Bigs in Blue: Police officer mentoring for middle-school students—Building trust and understanding through structured programming - Miner-Romanoff, Karen (Evaluation and program planning, 2023)
Clashes and tragedies between the police and citizens in recent years have focused greater attention on the increasingly negative interactions between community police officers and youth. The purpose of this paper is to describe the extensive evaluation of a New York City police mentoring program, Bigs in Blue (BIB), a component of Big Brothers Big Sisters of America. The evaluation will measure the success of the program with middle-school youth throughout the districts. Through police mentorship, BIB is intended to build youth’s skills and development and promote their trust in the police. The design is grounded in evidence-based studies of youth/officer programs. This paper describes the logic model, goals, program implementation, and comprehensive plans for quantitative and qualitative evaluation. Preliminary results of both quantitative and qualitative assessments of the New York BIB program indicated that positive change can take place on individual bases between youth and officers, with development of mutual trust and understanding, correction of prejudicial attitudes, and reduction of youth criminal behavior. Early findings of the BIB program showed promise for additional success. The evaluation described here accounts for measurement and input regarding all of the BIB program goals. With input from advisors in many related fields, each component of the evaluation has been refined to capture both quantitative and qualitative elements for tracking and improvement toward greater success. The BIB program offers young people not only opportunities for mentors but also more positive police branding and the building of mutual trust. The program brings responsible adults into challenging neighborhoods, and evaluations are necessary to track progress and institute improvements. •The evaluation described here accounts for measurement and input regarding the BIB program goals.•The BIB program offers young people opportunities for mentors and more positive police branding.•The program brings responsible adults into challenging neighborhoods.•Positive change can take place on individual bases between youth and officers.•The program leads to mutual trust, correction of prejudicial attitudes, and reduction of crime.